Pendampingan Para Lansia Melalui Metode Tafhim untuk Memahami Kandungan Al-Qur’an di Madrasah Uthmaniah Malaysia - Ahmadi, Ahmadi; Fillahi, Zidanizdan Yahya (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The goal of the Tafhim Method's senior mentorship program at Madrasah Uthmaniah in Penang, Malaysia, is to help the elderly understand the meaning and content of the Qur'an better. The Tafhim Method goes beyond simple reading comprehension to help the elderly understand Qur'anic passages through systematic design and pronunciation and tajweed. The study used the Asset-Based Community Development (ABCD) approach, which maximizes community assets, such as the expertise of the teachers and the passion of the participants in learning the Qur'an. The results of this program show that the application of the Tafhim Method, with references to tafsir books such as Tafsir Al-Azhar and Tafsir At-Tanwir, has a positive impact on the understanding of the elderly. They not only read the Qur'an correctly, but also understand its meaning, which is then applied in everyday life. This program is a significant step in supporting lifelong education for Muslim elderly.